Analisis faktor penyebab keterlambatan proyek pembangunan gedung berdasarkan perspektif penyedia jasa konstruksi pada Proyek Pembangunan RS PKU Muhammadiyah UNIMUDA Sorong - Alysia Wahyu Amalya; Athiah Safari; Intan Java Turis Repmi Tamsih (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Delay is one of the most common problems in construction projects and can lead to cost overruns, reduced work quality, and failure to meet the planned project completion schedule. This study aims to identify the factors causing delays and determine the most dominant factor affecting the Construction Project of PKU Muhammadiyah UNIMUDA Sorong Hospital. A descriptive quantitative method was employed, with data collected through questionnaires distributed to experts and professional employees from the contractor and consultant teams involved in the project. Out of a population of 40 individuals, 33 respondents met the criteria for analysis. The data were tested using the Kaiser-Meyer-Olkin (KMO) and Bartlett’s Test of Sphericity for validity, as well as Cronbach’s Alpha for reliability, and were subsequently analyzed using the Relative Importance Index (RII) method. The results identified nine factors with 31 valid and reliable criteria influencing construction project delays. Environmental/weather factors were found to be the most dominant, with an Adjusted RII value of 87.63%, followed by labor factors at 83.08% and material factors at 81.82%. These findings indicate that environmental and weather conditions pose the greatest risk to achieving project schedule targets, particularly because weather conditions and site characteristics can hinder resource mobilization and fieldwork activities. This study provides empirical evidence showing that environmental/weather factors are the most dominant cause of delays in building construction projects in the Southwest Papua region and can serve as a basis for developing delay risk mitigation strategies for projects with similar characteristics.